Strategic Decision Making and Organization Performance: A Literature Review - Alhawamdeh, Hamzeh M.; Alsmairat, Mohammad A.K. (International Review of Management and Marketing, 2019)
This paper aims to present and discuss the astrategic dissicion making and organization performance, by a review of the relevant literature has shown that a large number of previous studies have attempted to focuse on the importance of strategic dissicion making, in addition to what it is impact on the organization's performance. However, this study contributes to the understanding of factors, which influence managers, decision and performance like environment factors, leadership behavior, Organizational Justice, decision approach and process. The study concluded by reviewing the literature and previous studies indicate that the strategic decision-making process plays an important role in the effective performance of the organization.The studies also showed that the internal and external environmental factors that affect the performance of the managers to make strategic decisions , As well as , the using of decision support systems help decision-makers in providing the required information in time, which helps to raise the performance of the strategic decision that a direct impact on performance of the organization. Keywords: Strategic, Decision-making, Organizational Performance, Strategic Decision. JEL Classifications: M10; M15 DOI: https://doi.org/10.32479/irmm.8161